2009
DOI: 10.1111/j.1741-2358.2008.00228.x
|View full text |Cite
|
Sign up to set email alerts
|

Cartilaginous choristoma of the tongue

Abstract: Choristomas are lesions composed of normal cells or tissues occurring in an abnormal location. Cartilaginous choristomas of the oral mucosa are rare and occur preferentially on the tongue and less often in sites such as the soft palate and gingiva. Oral lesions are generally covered by integral mucosa and can occur at any age. The present study describes a case of a 73-year-old female presenting with an asymptomatic cartilaginous choristoma on the ventral surface of the tongue which had developed over a period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…There was no finding of malignancy such as atypical mitosis, binucleation, prominent nucleoli, nuclear pleomorphism or increased nuclear/cytoplasmic ratio. Therefore, total excision of the tumour is the treatment of choice for this neoplasm 5 6 8…”
Section: Discussionmentioning
confidence: 99%
“…There was no finding of malignancy such as atypical mitosis, binucleation, prominent nucleoli, nuclear pleomorphism or increased nuclear/cytoplasmic ratio. Therefore, total excision of the tumour is the treatment of choice for this neoplasm 5 6 8…”
Section: Discussionmentioning
confidence: 99%
“…This theory is particularly attractive for explaining lesions located on the lateral border, ventral surface or tip of the tongue, especially in an older age group [17,18,21,22,28,32,33]. Some papers have reported that traumatic cartilaginous metaplasia is also seen within flabby edentulous alveolar ridges in response to mechanical irritation caused by ill-fitting dentures [46,47].…”
Section: Discussionmentioning
confidence: 99%
“…Within the oral cavity, endogenous elements that might result in hamartomatous proliferations include smooth muscle (2, 3), vessels (4), nerves, lymphatics, skeletal muscle (5), fat (6), salivary tissue (7), and epithelium (8). Choristomatous elements in the oral cavity might include bone (9), cartilage (10), glial tissue (11, 12), and skin appendages (13). Glial tissue hamartomas were also described in the oral cavity (14) but these should have probably been better diagnosed as choristoma, because glial tissue is not a normal component of oral mucosa.…”
Section: Introductionmentioning
confidence: 99%